$\displaystyle n = 1,2,3...$

$\displaystyle I_{n} = \int \frac {x^{n-1}}{2-x} dx$ between limits 0 and 1.

Writing $\displaystyle x^{n} = x^{n-1}(2-(2-x))$, show this sequence satisfies $\displaystyle I_{n+1} = 2I_{n} - \frac {1}{n}$.

Now, I can't quite get a foothold into this puzzle. I'm thinking there's a simple logical step but I don't see it. Can someone help please? I wanted to try induction but I don't see how I'm supposed to use the idea they've told me to do so. It is required of the problem to use this hint.